'I'm Not that Kind of Doctor': On Being In-Between in a Global Health Intervention. Issue 1 (1st March 2019) - Nelson, Erica
Abstract : Within multi-disciplinary global health interventions, anthropologists find themselves navigating complex relationships of power. In this article, I offer a critical reflection on this negotiated terrain, drawing on my experience as an embedded ethnographer in a four-year adolescent sexual and reproductive health research intervention in Latin America. I critique the notion that the transformative potential of ethnographic work in global health remains unfulfilled. I then go on to argue that an anthropological practice grounded in iterative, inter-subjective and self-reflexive work has the potential to create 'disturbances' in the status quo of day-to-day global health practice, which can in turn destabilise some of the problematic hubristic assumptions of health reforms.